(untitled) (Journal of Economic Research & Business Administration, 2016)
New direction, which is different from the traditional financial systems, is Islamic finance. This direction develops also in our country. Though Islamic finance began to develop in muslim countries, today many European and Asian countries as Great Britain, South Korea and Japan implement them to their financial systems. As the main principles of Islamic finances are moral-ethical values, transparency and honesty, many non muslim consumers are also interested in it. The article discusses Islamic banking as one of important areas of Islamic Finance. Describes the types of banking products and services offered by Islamic Bank al Hilal Bank.